Mitochondrial Tim9 protects Tim10 from degradation by the protease Yme1. Issue 3 (19th May 2015) - Spiller, Michael P.; Guo, Liang; Wang, Qi; Tran, Peter; Lu, Hui
Abstract : Tim9 and Tim10 are essential homologue proteins forming a stable complex in mitochondria. The present study suggests that primary function of Tim9 is to protect Tim10 from degradation by Yme1 via assembly into the Tim9–Tim10 complex. Abstract : Translocase of IM (inner membrane; Tim)9 and Tim10 are essential homologue proteins of the mitochondrial intermembrane space (IMS) and form a stable hexameric Tim9–Tim10 complex there. Redox-switch of the four conserved cysteine residues plays a key role during the biogenesis of these proteins and, in turn, the Tim proteins play a vital chaperone-like role during import of mitochondrial membrane proteins. However, the functional mechanism of the small Tim chaperones is far from solved and it is unclear whether the individual proteins play specific roles or the complex functions as a single unit. In the present study, we examined the requirement and role for the individual disulfide bonds of Tim9 on cell viability, complex formation and stability using yeast genetic, biochemical and biophysical methods. Loss of the Tim9 inner disulfide bond led to a temperature-sensitive phenotype and degradation of both Tim9 and Tim10. The growth phenotype could be suppressed by deletion of the mitochondrial i-AAA (ATPases associated with diverse cellular activities) protease Yme1, and this correlates strongly with stabilization of the Tim10 protein regardless of Tim9 levels. Formation of both disulfide bonds is not essential for Tim9 function, but it can facilitate the formation and improve the stability of the hexameric Tim9–Tim10 complex. Furthermore, our results suggest that the primary function of Tim9 is to protect Tim10 from degradation by Yme1 via assembly into the Tim9–Tim10 complex. We propose that Tim10, rather than the hexameric Tim9–Tim10 complex, is the functional form of these proteins.